Wogonin increases doxorubicin sensitivity by down-regulation of IGF-1R/AKT signaling pathway in human breast cancer - Fu, P; Du, F; Liu, Y; Hong, Y; Yao, M; Zheng, S (Cellular and Molecular Biology, 2015)
Currently drug resistance has remained a major challenge in successful breast cancer therapy. Wogonin, one of the active components of scutellaria baicalensis, has shown anticarcinogenic, chemopreventive, and immunoregulatory functions. The present study aimed to explore whether wogonin exerted synergistic cytotoxicity with doxorubicin in breast cancer. Our data indicated that wogonin inhibited the proliferation of breast cancer cells in a dose- and time-dependent manner. Combined treatment with wogonin increased the doxorubicin sensitivity in breast cancer cells. Moreover, administration with wogonin alone or in combination with doxorubicin suppressed the expression of insulin like growth factor 1 receptor (IGF-1R) in Bcap-37 and MCF-7 cells. Incubation with insulin like growth factor (IGF) I or IGF-II promoted cell growth, which was reversed by wogonin co-administration. Mechanically, we found that down-regulation of IGF-1R diminished the chemosensitization role of wogonin in breast cancer. In addition, wogonin suppressed the phosphorylation levels of AKT and addition of AKT inhibitor abolished the synergistic cytotoxicity of wogonin and doxorubicin. Taken together, combined treatment with wogonin increased the doxorubicin sensitivity in breast cancer cells through regulation of IGF-1R/AKT signaling pathway. Therefore, these findings demonstrated that combination therapy with wogonin led to better therapeutic effects via regulating IGF-1R/AKT signaling pathway in doxorubicin-based chemotherapy for breast cancer.